Who's the Boss? Strengthening the effectiveness of capacity-development support - Niels Keijzer (Deutsches Institut für Entwicklungspolitik (DIE), 2013)
Development cooperation encompasses a multitude of accountability relations that do not automatically complement one another. In practice, the strong accountability needs of donor constituencies create perverse incentives to bypass developing-country institutions in an effort to seek “value for money” for “their” development assistance. This reality contrasts with international commitments made to use country systems – i.e. developing countries' own arrangements and procedures for public sector planning, budgeting and accountability – as the default option for development assistance. During the 2011 High Level Forum on Aid Effectiveness in Busan, the strengthening of effective institutions was identified as a principal means for improving accountability; the process of strengthening institutions should be led by developing countries, whereas donors committed to providing capacity-development (CD) support. Most of this support comes in the form of technical cooperation, which takes up a large chunk of official development assistance (ODA). This includes a large variety of actions, including training, twinning, studies and – taking up the bulk of the assistance – short- or long-term experts. It was recognised during discussions in Busan that the effectiveness of CD support ultimately depends on the quality of the relationship between the parties involved. In the public sector, this implies optimising the use of country systems. Seven fundamental changes should be sought to ensure effective and accountable CD support: 1. Ensure that developing countries lead in identifying and articulating demand for CD support. 2. Jointly discuss all possible options for CD support and be fully transparent on financial details for each. 3. Jointly identify CD support objectives and the approach to financing, and make these details available to all relevant stakeholders. 4. Phase out formal and informal tying of support. 5. Regardless of the procurement approach chosen, ensure that developing countries lead recruitment decisions for CD support. 6. Clarify managerial responsibility and ensure that support is primarily accountable to beneficiaries. 7. Ensure full developing-country involvement in monitoring and evaluation of CD support, and that monitoring promotes variation and adaption. Developing countries and their international partners can gain much from pursuing these changes. Optimising the use of country systems presents costs to all involved, but not paying these is clearly more expensive. Despite the lapse of international interest in the aidand development-effectiveness agenda, a stronger and context-sensitive promotion of the use of country systems for CD support remains important, given the strong investments made and the many partners involved
Keywords: 330